Oral health status of children and young adults with maple syrup urine disease in Turkey - Elif Ballikaya; Yılmaz Yildiz; Nagihan Koç; Ayşegül Tokatli; Meryem Uzamis Tekcicek; Hatice Serap Sivri (BMC, 2021)
Abstract Background Maple syrup urine disease (MSUD) is an inherited disorder clinically characterized by ketoacidosis, seizures, coma, psychomotor delay, and intellectual disability. The treatment requires a life-long protein-restricted diet, rich in carbohydrates and fats, supplemented with a medical amino acid formula. Diet, oral health and general health influence each other in a vicious cycle. The aim of this study was to investigate the oral health status of children and young adults with MSUD in Turkey. Methods A descriptive study was conducted on patients with MSUD who applied for routine follow-up to the pediatric metabolic diseases clinic at Hacettepe University, Children's Hospital in Ankara, Turkey in a 12-month period. Patients with any other concomitant genetic diseases and acute infection were excluded. A total of twenty-five patients were enrolled and underwent oral examination including DMFT/S, dmft/s (decayed/missing/filled teeth/surfaces for deciduous and primary teeth, respectively), plaque and gingival indices. Panoramic radiographs were obtained in 12 cooperative patients. Results Mean age was 9.88 ± 5.68 s.d years. More than half of the parents had only primary school level education, and low income. Fourteen patients consumed medical formula during or right before sleep. Fourteen patients reported caries-associated pain. Gingival inflammation was present in all 15 patients who cooperated for evaluation. Seven out of twelve patients had at least one dental anomaly or alterations in mandibular morphology. Five patients had previously been treated for caries under general anesthesia. To our knowledge, this is the first study to document oral clinical and radiologic findings in patients with MSUD. Conclusions Impaired oral health was observed in this rare disease population. Regular dental referral by physicians, preventive measures and dental treatments should be included in multidisciplinary management of maple syrup urine disease to promote oral health.